Analisis Rasio Keuangan Dalam Menilai Kinerja Keuangan : (Studi Kasus Pada PT Arthavest Tbk Yang Terdaftar Di BEI Tahun 2018-2022) - Reza Santika; Rizka Ayuni; Titin Trisnawati (Universitas Katolik Widya Karya Malang, 2024)
This research is entitled Financial Ratio Analysis in Assessing Financial Performance (Case Study of PT. Arthavest Tbk Listed on the IDX 2018-2022). The purpose of this research is to find out how the company PT. Arthavest Tbk for the 2018-2022 period using Liquidity Ratios, Activity Ratios and Profitability Ratios. This research method is descriptive research with a quantitative approach, namely by collecting, processing and interpreting the data obtained so that you can get a clear picture of the situation being studied based on numbers. The data collection technique is obtained from documentary evidence which contains data relevant to the object of the research carried out, namely by collecting PT financial report data. Arthavest Tbk. obtained from the Indonesian Stock Exchange (BEI) website, namely www.idx.co.id. The results of this research indicate that PT. Arthavest Tbk for the 2018-2022 period tends to remain unstable, however, the company's liquidity ratio has been able to fulfill its short-term obligations by obtaining current assets that are greater than its current liabilities